Filsafat Pendidikan John Dewey dan Implikasinya terhadap Pendidikan Nasional - Ahmad Samawi (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
John Dewey's Philosophy of Education and Its Implications to National Education. John Dewey is most productive educator-thinker in the United States. Sometimes his philosophy of education is called pragmatism in terms of his intention on practical utilities for human lives. Thinking seems to be a central focus in his theory and an instrument for measuring progresses so that his thought is also called instrumentalism and progressivism. His most important thought is democratization in education. Beside its negative aspects, the thought contains positive aspects valuable for developing our national education based on the Pancasila.